Prevalence of variations in melanoma susceptibility genes among Slovenian melanoma families - Besic Nikola; Zgajnar Janez; Novakovic Srdjan; Cerkovnik Petra; Peric Barbara; Hocevar Marko (BMC, 2008)
Abstract Background Two high-risk genes have been implicated in the development of CM (cutaneous melanoma). Germline mutations of the CDKN2A gene are found in < 25% of melanoma-prone families and there are only seven families with mutation of the CDK4 gene reported to date. Beside those high penetrance genes, certain allelic variants of the MC1R gene modify the risk of developing the disease. The aims of our study were: to determine the prevalence of germline CDKN2A mutations and variants in members of families with familial CM and in patients with multiple primary CM; to search for possible CDK4 mutations, and to determine the frequency of variations in the MC1R gene. Methods From January 2001 until January 2007, 64 individuals were included in the study. The group included 28 patients and 7 healthy relatives belonging to 25 families, 26 patients with multiple primary tumors and 3 children with CM. Additionally 54 healthy individuals were included as a control group. Mutations and variants of the melanoma susceptibility genes were identified by direct sequencing. Results Seven families with CDKN2A mutations were discovered (7/25 or 28.0%). The L94Q mutation found in one family had not been previously reported in other populations. The D84N variant, with possible biological impact, was discovered in the case of patient without family history but with multiple primary CM. Only one mutation carrier was found in the control group. Further analysis revealed that c.540C>T heterozygous carriers were more common in the group of CM patients and their healthy relatives (11/64 vs. 2/54). One p14ARF variant was discovered in the control group and no mutations of the CDK4 gene were found. Most frequently found variants of the MC1R gene were T314T, V60L, V92M, R151C, R160W and R163Q with frequencies slightly higher in the group of patients and their relatives than in the group of controls, but the difference was statistically insignificant. Conclusion The present study has shown high prevalence of p16INK4A mutations in Slovenian population of familial melanoma patients (37%) and an absence of p14ARF or CDK4 mutations.